Pengaruh Green Finance, Green Accounting dan Aktivitas Tanggung Jawab Sosial terhadap Kinerja Keberlanjutan di Indonesia - Meliyanti; Regina J. Arsjah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study examines the influence of green finance, green accounting, and corporate social responsibility (CSR) activities on the sustainability performance of banking sector companies in Indonesia. Using the Random Effect Model (REM) with the STATA 17 software, and a sample of 13 publicly listed banking companies in Indonesia from 2019 to 2023, the results show that green finance and CSR do not have a positive impact on sustainability performance. In contrast, green accounting has a positive effect on sustainability performance. However, the results for all three variables were not significant, which contradicts previous studies. This discrepancy suggests that other factors may be influencing the sustainability performance of companies in the banking sector. The study highlights that the activities conducted by companies are not yet sufficient to optimally support sustainability performance.